Agrare Betriebsformen im Vorland des Tien-Schan - Giese, Ernst (ERDKUNDE, 1968)
The agriculture of Soviet Central Asia is limited by the aridity and marked continentality of the climate. Therefore, the structure and the aims of production of the kolkhozes and sovkhozes of the Tien-Shan foreland are primarily determined by the utilization of melt waters flowing down from the snow and ice region of the Tien-Shan in spring and summer. On the basis of irrigation farming the foreland with its extremely fertile loess-plains has developed into one of the most important agricultural regions of Central Asia. In the western foreland of the Tien-Shan with its great quantities of radiation and heat and long growing seasons cotton is the chief irrigated crop (oases of Fergana, Taskent, Chimkent). Sugar beet, tobacco, fruit, vegetables, corn and vineyards occupy the irrigated land of the eastern oases, where climatic conditions are not so favourable for the growing of cotton. The share of irrigation farming is 2h of the area under cultivation, the remainder is under corn in dry farming (Bogar farming). In the kolkhozes and sovkhozes the keeping of livestock involves alpine pasturing as well as transhumance. As an example of the Tien-Shan piedmont region the foreland of the Zailiyskiy Alatau near Alma-Ata is described. Types of connective farms are illustrated in detail by the kolkhozes Voroshilov and Luch Vostoka.